PLASTICIDADE DA CULTURA DA SOJA (ð˜Žð˜ð˜ºð˜¤ð˜ªð˜¯ð˜¦ ð˜®ð˜¢ð˜¹ (L.) Merrill) EM DIFERENTES ARRANJOS ESPACIAIS - Heiffig, LÃlia Sichmann; CÃ¢mara, Gil Miguel de Sousa; Marques, Luciana Aparecida; Pedroso, Daniel Botelho; Piedade, SÃ´nia Maria de StÃ©fano (REVISTA DE AGRICULTURA, 2020)
PLASTICIDADE DA CULTURA DA SOJA (ð˜Žð˜ð˜ºð˜¤ð˜ªð˜¯ð˜¦ ð˜®ð˜¢ð˜¹ (L.) Merrill) EM DIFERENTES ARRANJOS ESPACIAIS